High EVI1 Expression Predicts Adverse Outcomes in Children With De Novo Acute Myeloid Leukemia - Zheng, Yongzhi; Huang, Yan; Le, Shaohua; Zheng, Hao; Hua, Xueling; Chen, Zaisheng; Feng, Xiaoqin; Li, Chunfu; Zheng, Mincui; Xu, Honggui; He, Yingyi; He, Xiangling; et al. (Frontiers in Oncology, 2021)
Background:High ecotropic viral integration site 1 (EVI1) expression (EVI1high) is an independent prognostic factor in adult acute myeloid leukemia (AML). However, little is known on the prognostic value of EVI1high in pediatric AML. This study aimed to examine the biological and prognostic significance of EVI1high in uniformly treated pediatric patients with AML from a large cohort of seven centers in China. Methods:A diagnostic assay was developed to determine the relative EVI1 expression by a single real-time quantitative polymerase chain reaction in 421 newly diagnosed pediatric AML patients younger than 14 years from seven centers in southern China. All patients were treated with a uniform protocol, but only 383 patients were evaluated for treatment response. Results:EVI1high was found in 9.0% of all 421 pediatric patients with de novo AML. EVI1high was predominantly found in acute megakaryoblastic leukemia (FAB M7), MLL rearrangements, and unfavorable cytogenetic aberrance, whereas it was mutually exclusive with t (8; 21), inv (16) / t (16; 16), CEBPA, NPM1, or C-KIT mutations. In the univariate Cox regression analysis, EVI1high had a significantly adverse 5-year event-free survival (EFS) and overall survival OS (hazard ratio [HR] = 1.821 and 2.401, p = 0.036 and 0.005, respectively). In the multivariate Cox regression analysis, EVI1high was an independent prognostic factor for OS (HR = 2.447, p = 0.015), but not EFS (HR = 1.556, p = 0.174). Furthermore, EVI1high was an independent adverse predictor of OS and EFS in patients with MLL rearrangements (univariate analysis: HR = 9.921 and 7.253, both p < 0.001; multivariate analysis: HR = 7.186 and 7.315, p = 0.005 and 0.001, respectively). Hematopoietic stem cell transplantation (HSCT) after the first complete remission (CR1) provided EVI1high patients with a tendential survival benefit compared to chemotherapy as a consolidation (5-year EFS: 68.4% vs. 50.8%, p = 0.26; 5-year OS: 65.9% vs. 54.8%, p = 0.45). Conclusion:It could be concluded that EVI1high can be detected in ～10% of pediatric AML cases. It is predominantly present in unfavorable cytogenetic subtypes and predicts adverse outcomes. Whether pediatric patients with EVI1high AML can benefit from HSCT in CR1 needs to be researched further.